OTORITAS KYAI DALAM MENENTUKAN KARAKTERISTIK MODEL PONDOK PESANTREN DARUSSALAM BLOKAGUNG BANYUWANGI - Fauzi, Rizki Miftakhudin (JURNAL AL-IJTIMAIYYAH, 2018)
Kyai, in the tradition of boarding schools to be a central figure. In addition to leading Islamic boarding schools, the term kyai relates to a title that is emphasized on glory and voluntary recognition of someone who is qualified in Islamic science as a cultural leader of society. If the cleric figure is interpreted as understanding above, it is necessary to study the figure of the clerics in determining the style of an institution, in this case the authority of the clerics in the pesantren. This study aims to find out the authority of the clerics in determining the characteristic models of the Darussalam Islamic Boarding School in Blokagung Banyuwangi. The research method uses a qualitative approach. In this study it can be concluded that the form of clerical authority in Darussalam Blokagung Banyuwangi Islamic boarding school is directed at religion, political attitudes, education and teaching. The direction was in the form of policies and advice which were then carried out in the leadership activities. The characteristics of Darussalam Blokagung Banyuwangi Islamic boarding school are included in the characteristics of a modern cottage, where Islamic boarding schools maintain a salaf cottage model while adding curriculum from the government.Keywords:  Authority, Kyai, Model, Pondok Pesantren